HUBUNGAN POLA TIDUR DENGAN GEJALA GASTRITIS PADA SANTRIWATI DI PONDOK PESANTREN AL-JAWAHIR CIPUTAT, TANGERANG SELATAN - Laraswati, Ayu; Azhary, Muhamad Al; Selvia, Akub (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2024)
ABSTRACTWorld Health Organization (WHO) 2019 stated that the gastritis symptom in the world is around 1.8-2.1 million people each year, the percentage of the gastritis symptom in Indonesia is 40.8%. Gastritis is an inflammation of the stomach wall, one of the causes is the habit of sleeping patterns. The purpose of this study was to determine the relationship between sleep patterns and the gastritis symptom. The research method used is quantitative with an analytic design and a cross-sectional approach using a questionnaire with the aim of knowing the relationship between sleep patterns (independent variable) and the gastritis symptom (dependent). The number of samples consisted of 33 female students at the Al-Jawahir Ciputat Islamic Boarding School, Tangerang Selatan in 2023. The sampling technique used was total sampling. The results showed that most female students had bad sleep patterns with a total of 27 respondents (81.8%) and most female students experienced gastritis with a total of 29 respondents (87.9%). The statistical test results obtained a p-value of 0.000 α = 0.05, so it can be concluded that there is a significant relationship between sleep patterns and the gastritis symptom. Suggestions from the authors are that it is hoped that the sleep patterns of adolescents can be maintained properly so that they can reduce the gastritis symptom. Keywords: Female Students, Gastritis Symptom, Sleep Pattern ABSTRAKWorld Health Organization (WHO) tahun 2019 menyebutkan bahwa gejala gastritis di dunia sekitar 1,8-2,1 juta jumlah penduduk setiap tahunnya, persentase dari angka gejala gastritis di Indonesia yaitu 40,8%. Gastritis merupakan peradangan pada dinding lambung, salah satu penyebabnya ialah kebiasaan pola tidur. Tujuan penelitian ini adalah untuk mengetahui hubungan pola tidur dengan gejala gastritis. Metode penelitian yang digunakan berupa kuantitatif dengan desain analitik dan pendekatan cross sectional menggunakan kuisioner dengan tujuan untuk mengetahui hubungan antara pola tidur (variabel independen) dengan gejala gastritis (dependen). Jumlah sampel terdiri dari 33 santriwati di Pondok Pesantren Al-Jawahir Ciputat,Tangerang Selatan tahun 2023. Teknik sampling yang digunakan adalah total sampling.Hasil penelitian didapatkan sebagian besar santriwati memiliki pola tidur buruk dengan jumlah 27 responden (81,8%) dan sebagian besar santriwati mengalami gejala gastritis dengan jumlah 29 responden (87,9%). Hasil uji statistik diperoleh nilai p-value 0,000 α = 0,05, maka dapat disimpulkan terdapat hubungan yang signifikan antara pola tidur dengan gejala gastritis. Saran dari penulis diharapkan pola tidur para remaja dapat terjaga dengan baik sehingga bisa mengurangi gejala gastritis. Kata Kunci: Gejala Gastritis, Pola Tidur, Santriwati